Place relationships in a wilderness setting: an analysis of two mountaineering camps in the Canadian Rocky Mountains. Issue 2 (3rd April 2017) - Reid, Robin; Palechuk, Terry
ABSTRACT: This paper presents two mountaineering camps in the Canadian Rockies as relevant sites for consideration of concepts of place meaning, place attachment and motivational theories associated with participants attending these camps in the summer of 2013. Of particular interest is why people select these mountaineering camps as a holiday experience and what is it about the camps that keeps them coming back? Analysis of survey results of camp participants provide insight into participant motivations and the place meaning attached to the sites where these mountaineering activities take place. Findings build upon current research and support the hypothesis that natural settings are imbued with place meaning within outdoor recreational contexts.